La question de et dans la codification graphique du castillan et dans celle d’autres langues romanes d’Espagne - Sophie Sarrazin (Lengas, 2019)
This paper questions the weight exercised by the normative models of a dominant language in emancipation processes initiated by languages that have endured long periods of diglossic subjection. It examines, first, the question of the graphic codification of and in Castilian (settled at the beginning of the eighteenth century by the Real Academia Española) and in a second time, the treatment of the question in recent graphic proposals for four Romance languages (Aragonese, Astur-Leonese, Catalan, Galician).